2023
DOI: 10.1111/sum.12976
|View full text |Cite
|
Sign up to set email alerts
|

Cover crops and soil loosening are key components for managing P and C stocks in agricultural soils

Tuomas J. Mattila

Abstract: Agricultural soils have accumulated phosphorus (P) and lost carbon (C) in the recent decades. Simultaneously, soil structure has been degraded by the large increase in machinery weight. High wheel loads compact the subsoil, resulting in reduced root growth, decreased yields, and hence decreased C inputs and P removals. To reduce the accumulated excess P stock, the P balance should be kept strongly negative for decades, which requires high biomass production. P accumulation in poorly yielding field parts has cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Modeling P drawdown in a forage system found that drawdown estimates were highly variable, but that lowering soil P from "excess" to "target" levels in that study would require an average of 7 to 15 years in a nonlinear fashion (Schulte et al 2010). Additionally, within-field variability of legacy P loss and drawdown potential can be very high, partly because of within-field yield potential differences (Mattila 2023).…”
Section: Resultsmentioning
confidence: 82%
“…Modeling P drawdown in a forage system found that drawdown estimates were highly variable, but that lowering soil P from "excess" to "target" levels in that study would require an average of 7 to 15 years in a nonlinear fashion (Schulte et al 2010). Additionally, within-field variability of legacy P loss and drawdown potential can be very high, partly because of within-field yield potential differences (Mattila 2023).…”
Section: Resultsmentioning
confidence: 82%